A comparative computational study of blood flow pattern in exemplary textile vascular grafts. Issue 7 (3rd July 2018) - Valencia, Raúl A.; García, Manuel J.; Bustamante, John
Abstract: Textile vascular grafts are biomedical devices and play an important role serving as a solution for the partial replacement of damaged arterial vessels. It is believed that the success of a textile vascular graft, in the healing process after implantation, is due to the porous micro-structure of the wall. Although the transport of fluids through textiles is of great technical interest in biomedical applications, little is known about predicting the micro-flow pattern and cellular transport through the wall. The aim of this work is to investigate how the type of fabric, permeability and porosity affect both the local fluid dynamics at several scales and the fluid-particle interaction between platelets in textile grafts, related with the graft occlusion. This study involves both experimental and computational tests. Experimental tests are performed to characterize the permeability and porosity according to the ISO 7198 standard. The numerical process is based on a multi-scale approach where the fluid flow is solved with the Finite Element Method and the discrete particles are solved with the Molecular Dynamic Method. The results have shown that the type of fabric in textile vascular grafts and the degree of porosity and permeability affect both the local fluid dynamics and the level of penetration of platelets through the wall, thus indicating their importance as design parameters.